Application of Adult Learning Theory to Supplemental Instruction in Undergraduate Chemistry Classes - Robert F. Reardon; Tereza Christina C. Valverde (Adult Education Research Conference, 2013)
The Supplemental Instruction (SI) program relies on the foundations of adult education. In particular it depends heavily on peer support in difficult classes. The andragogical approach highlights the importance of addressing different learning styles and helps students to engage in collaborative learning and problem solving.